A support grouting material
By combining fast hard high-iron sulfaluminate cement with ordinary silicate cement in the support grouting materials and combining a variety of modifiers, a high-flexural resistance and early strength support grouting material is prepared, which solves the problems of low flexural strength and unstable existing materials, and achieves high strength and long-term durability of the support.
Patent Information
- Application Number
- CN202411802310.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The flexural strength of the existing support grouting materials is low and unstable, and there is a later reversal phenomenon, which affects the long-term safety performance of the support.
A fast gel material system is used to combine fast hard high-iron sulfaluminate cement and ordinary silicate cement with fast-gel material, combined with expansion hydration accelerator, silica fume, quartz sand, superplasticizer, retarder, viscosity modifier, premature strength agent and defoaming agent, and through scientific combination and synergistic action, a high-flexural resistance and high-premature strength support grout material is prepared.
It has achieved the early characteristics of the support grouting material with high flexural compressive strength, high flow, compactness, good anti-secretion of water secretion, slightly expanded, and good long-term durability. It is suitable for gravity grouting of railroad bridge spherical support and expressway support.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to a cement-based material, in particular to a support grouting material, and belongs to the technical field of building materials. Background Art
[0002] In the bridge construction design of the railway passenger dedicated line, the spherical bearings of the railway bridge need to be installed with bearing grouting materials. According to the requirements of TB / T 3320-2013 "Spherical Bearings of Railway Bridges", the bearing grouting materials must have certain flexural properties, and clearly require that the 1-day and 28-day flexural strengths are greater than or equal to 10MPa, and have high early and late flexural strengths. The strength does not shrink, which is an important guarantee for its safety and durability. At the same time, the bearing grouting materials should also have good workability and high hourly strength. At present, most of the bearing grouting materials on the market can achieve good workability and high hourly strength, but the flexural strength is low or unstable, and there is a phenomenon of late shrinkage, which poses a hidden danger to the long-term safety performance of the bearing. Summary of the invention
[0003] In view of the defects of existing bearing grouting materials such as low flexural strength and instability, the purpose of the present invention is to provide a bearing grouting material with high flexural strength and high early strength. The bearing grouting material has the characteristics of high early flexural strength, high compressive strength, high fluidity, self-flowing and compacting, good resistance to water seepage and segregation, micro-expansion, and good long-term durability. It is suitable for gravity grouting of spherical bearings of railway bridges and highway bearings.
[0004] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0005] A bearing grouting material, comprising the following components by weight:
[0006] 5~20 parts of ordinary Portland cement;
[0007] 30-50 parts of rapid hardening high iron sulphoaluminate cement;
[0008] 3-5 parts of swelling hydration accelerator;
[0009] Silica fume 2~6 parts;
[0010] 30~50 parts of quartz sand;
[0011] Superplasticizer 0.2~0.6 parts;
[0012] Retarder 0.2~0.5 parts;
[0013] Viscosity modifier 0.01~0.03 parts;
[0014] Early strength agent 0.04~0.2 parts;
[0015] Defoaming agent 0.1~0.3 parts;
[0016] The swelling hydration accelerator is prepared by mixing quicklime, over-burned gypsum, triisopropanolamine and sodium octadecanoate, and grinding the mixture in a mill until the specific surface area is ≥350m 2 / kg; the overburned gypsum is made by roasting at 300-350°C;
[0017] The viscosity modifier is a complex of hydroxypropyl methylcellulose ether and L-galactose.
[0018] Furthermore, the CaO content in the quicklime is ≥ 60%.
[0019] Furthermore, the mass ratio of quicklime, overburned gypsum, triisopropanolamine and sodium octadecanoate is 60-80:20-40:1-3:0.6-1.0.
[0020] Quicklime dissolves to form calcium hydroxide when it meets water. This reaction is very rapid. In order to control the hydration speed of quicklime, while grinding quicklime and over-burned gypsum, an appropriate amount of triisopropanolamine and sodium octadecanoate are added and ground together for modification, so that the surface of the fine particles of quicklime and over-burned gypsum is coated with a layer of film. The hydrophobicity of the film prevents direct contact between water and lime particles. When the membrane-modified lime component meets water, the sodium octadecanoate wrapped on the surface of the lime particles will slowly dissolve, and the lime particles will contact water and start digestion reaction. The solubility of over-burned gypsum in water is very small, and the hydration reaction ability is also very slow. However, due to the digestion reaction of lime and the alkaline environment provided by cement hydration, the reaction ability of over-burned gypsum is stimulated and the dissolution rate of over-burned gypsum is accelerated. The activity of over-burned gypsum fired at different temperatures is different. The over-burned gypsum fired at low temperature has lattice structure defects, which can accelerate its hydration dynamic process. When it meets water, it hydrates into dihydrate gypsum faster, while the over-burned gypsum fired at high temperature is very stable because it has no crystal structure defects. Ordinary Portland cement and fast-hardening high-iron sulfoaluminate cement generate ettringite through hydration reaction with water. The digestion reaction products of lime and dissolved overburned gypsum will participate in hydration during the cement hydration process. Triisopropanolamine can accelerate the cement hydration reaction and promote the rapid formation of ettringite. The large amount of ettringite generated gives the grouting material excellent early strength properties, so that the grouting material has very high early flexural and compressive strengths. The digestion products of calcium hydroxide and ettringite crystals will produce a certain expansion, which can compensate for the shrinkage, so that the grouting material has a micro-expansion property as a whole. At the same time, overburned gypsum can supplement enough sulfur elements, so that the generated ettringite can maintain a stable structure, without crystal conversion phenomenon, no shrinkage, good later stability, and thus improve long-term durability.
[0021] Furthermore, the silica fume particle size is 0.2-0.4 μm. Silica fume greatly reduces the pore size in the hydrated slurry, can improve the pore size distribution, and the filling effect on the pores of cement mortar particles can improve the density of the grouting material, which is conducive to improving the flexural strength; at the same time, silica fume has a certain water retention performance, can improve the workability of the grouting material, and can reduce the water seepage and segregation of the grouting material.
[0022] Furthermore, the quartz sand is compounded by quartz sand of 10-20 mesh, 20-40 mesh, and 50-100 mesh particle sizes, and the mass percentages thereof are 30-55%: 20-40%: 15-35% respectively.
[0023] Furthermore, the superplasticizer is a polycarboxylic acid high-performance water-reducing agent. The polycarboxylic acid high-performance water-reducing agent has excellent water-reducing performance, which enables the bearing grouting material to have excellent fluidity at a lower water-cement ratio, can be self-flowing and dense, and can greatly improve the construction efficiency.
[0024] Furthermore, the retarder is at least one of tartaric acid, boric acid and sodium gluconate.
[0025] Furthermore, the mass percentage of hydroxypropyl methylcellulose ether and L-galactose is 40-60%:40-60%. The composite viscosity modifier of hydroxypropyl methylcellulose ether and L-galactose can enhance the anti-settling force and anti-bleeding and segregation performance of the grouting material, so that the grouting material has excellent working performance.
[0026] Furthermore, the early strength agent is at least one of lithium carbonate, lithium sulfate and calcium formate.
[0027] Furthermore, the defoaming agent is a silicone defoaming agent.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The high-flexural and high-early-strength bearing grouting material of the present invention adopts a quick-hardening high-iron sulphoaluminate cement and ordinary Portland cement compounded quick-hardening cement system, so that it has a long operability time and very high early flexural and compressive strength. The appropriate proportion of ordinary Portland cement can ensure that the strength of the bearing grouting material can develop stably and the strength will not shrink in the later stage.
[0030] (2) The high-flexural and high-early-strength bearing grouting material of the present invention stimulates the reaction ability of the overburned gypsum and accelerates the dissolution rate of the overburned gypsum through the slow digestion reaction of the membrane-modified lime in the expansive hydration promoter. The digestion reaction products of the lime and the dissolved overburned gypsum participate in hydration during the cement hydration process. Triisopropanolamine can accelerate the cement hydration reaction and promote the rapid formation of calcium sulfonate. The large amount of calcium sulfonate generated gives the grouting material excellent early strength performance, so that the grouting material has very high early flexural and compressive strength. The digestion products of calcium hydroxide and calcium sulfonate crystals will produce a certain expansion, which can compensate for the shrinkage, so that the grouting material has a micro-expansion performance as a whole. At the same time, the overburned gypsum can supplement sufficient sulfur elements, so that the generated calcium sulfonate can maintain a stable structure, will not experience crystal transformation phenomenon, will not shrink, and has good later stability, thereby improving long-term durability.
[0031] (3) Adding silica fume to the high-flexural and high-early-strength bearing grouting material of the present invention can improve the pore size distribution, and the filling effect on the pores of cement mortar particles can improve the compactness of the bearing grouting material, which is conducive to improving the flexural strength. At the same time, silica fume has a certain water retention performance, which can improve the workability of the bearing grouting material and reduce the water seepage and segregation of the grouting material.
[0032] (4) The high-flexural and high-early-strength bearing grouting material of the present invention has excellent working performance through the synergistic effect of the polycarboxylic acid high-performance water-reducing agent and the viscosity modifier, and can be self-flowing and dense, which can greatly improve the construction efficiency.
[0033] (5) The high-flexural and high-early-strength bearing grouting material of the present invention achieves a suitable balance between construction operability and 2h early strength by compounding a retarder and an early-strength agent, thereby meeting the purpose of on-site workability and early strength technical requirements.
[0034] Through scientific combination and synergistic enhancement of the components, the high-flexural and high-early-strength bearing grouting material has the characteristics of high early flexural strength, high compressive strength, high fluidity, self-flowing and compacting, good resistance to water seepage and segregation, micro-expansion, and good long-term durability. It is suitable for gravity grouting of spherical bearings of railway bridges and highway bearings. DETAILED DESCRIPTION
[0035] The present invention is further illustrated by the following examples, but the protection scope of the present invention is not limited to the following examples.
[0036] In the following specific examples, unless otherwise specified, all raw materials are directly purchased commercial raw materials. For example, polycarboxylic acid high-performance water reducer was purchased from Sika Company; fast-hardening high-iron sulphoaluminate cement was purchased from Zhengzhou Jianwen Special Materials Technology Co., Ltd.; fast-setting and fast-hardening sulphoaluminate cement was purchased from Tangshan Polar Bear Building Materials Co., Ltd., etc.
[0037] Example 1
[0038] 1. Preparation of swelling hydration accelerator:
[0039] Mix 60 parts of quicklime, 40 parts of overburned gypsum (calcined at 320°C), 1 part of triisopropanolamine and 0.6 parts of sodium octadecanoate, and grind them in a mill for 30 minutes until the specific surface area is ≥350m 2 / kg, the obtained powder is the swelling hydration accelerator.
[0040] 2. Preparation of bearing grouting material:
[0041] 5 parts of PO52.5 ordinary Portland cement, 45 parts of R·FAC42.5 fast-hardening high-iron sulphoaluminate cement, 3 parts of expansive hydration accelerator, 2 parts of silica fume (0.3μm), 45 parts of quartz sand (10~20 mesh: 20~40 mesh: 50~100 mesh = 40%: 30%: 30%), 0.3 parts of polycarboxylic acid high-performance water reducer, 0.2 parts of sodium gluconate retarder, 0.02 parts of viscosity modifier (hydroxypropyl methylcellulose ether: L-galactose = 50:50), 0.1 parts of lithium carbonate early strength agent, and 0.2 parts of silicone defoaming agent.
[0042] Example 2
[0043] 1. Preparation of swelling hydration accelerator:
[0044] Mix 70 parts of quicklime, 30 parts of overburned gypsum (calcined at 320°C), 2 parts of triisopropanolamine and 0.8 parts of sodium octadecanoate and grind them in a mill for 30 minutes until the specific surface area is ≥350m 2 / kg, the obtained powder is the swelling hydration accelerator.
[0045] 2. Preparation of bearing grouting material:
[0046] PO42.5 ordinary Portland cement 10 parts, R·FAC52.5 fast-hardening high-iron sulphoaluminate cement 40 parts, expansive hydration accelerator 3 parts, silica fume (0.3μm) 2 parts, quartz sand 45 parts (10~20 mesh: 20~40 mesh: 50~100 mesh = 40%: 30%: 30%), polycarboxylic acid high-performance water reducer 0.3 parts, sodium gluconate retarder 0.2 parts, viscosity modifier (hydroxypropyl methylcellulose ether: L-galactose = 50:50) 0.03 parts, lithium sulfate early strength agent 0.1 parts, silicone defoamer 0.1 parts.
[0047] Example 3
[0048] 1. Preparation of swelling hydration accelerator:
[0049] Mix 80 parts of quicklime, 20 parts of overburned gypsum (calcined at 320°C), 3 parts of triisopropanolamine and 1 part of sodium octadecanoate, and grind them in a mill for 30 minutes until the specific surface area is ≥350m 2 / kg, the obtained powder is the swelling hydration accelerator.
[0050] 2. Preparation of bearing grouting material:
[0051] 15 parts of PO52.5 ordinary Portland cement, 30 parts of R·FAC42.5 fast-hardening high-iron sulphoaluminate cement, 5 parts of expansive hydration accelerator, 5 parts of silica fume (0.2μm), 45 parts of quartz sand (10~20 mesh: 20~40 mesh: 50~100 mesh = 40%: 30%: 30%), 0.2 parts of polycarboxylic acid high-performance water reducer, 0.5 parts of boric acid retarder, 0.03 parts of viscosity modifier (hydroxypropyl methylcellulose ether: L-galactose = 40:60), 0.2 parts of calcium formate early strength agent, and 0.2 parts of silicone defoaming agent.
[0052] Example 4
[0053] 1. Preparation of swelling hydration accelerator:
[0054] Mix 60 parts of quicklime, 40 parts of overburned gypsum (calcined at 320°C), 1 part of triisopropanolamine and 0.6 parts of sodium octadecanoate, and grind them in a mill for 30 minutes until the specific surface area is ≥350m 2 / kg, the obtained powder is the swelling hydration accelerator.
[0055] 2. Preparation of bearing grouting material:
[0056] 18 parts of PO52.5 ordinary Portland cement, 30 parts of R·FAC42.5 fast-hardening high-iron sulphoaluminate cement, 3 parts of expansive hydration accelerator, 4 parts of silica fume (0.3μm), 45 parts of quartz sand (10~20 mesh: 20~40 mesh: 50~100 mesh = 50%: 30%: 20%), 0.5 parts of polycarboxylic acid high-performance water reducer, 0.4 parts of tartaric acid retarder, 0.02 parts of viscosity modifier (hydroxypropyl methylcellulose ether: L-galactose = 60:40), 0.1 parts of lithium carbonate early strength agent, and 0.2 parts of silicone defoaming agent.
[0057] Comparative Example 1
[0058] The difference between this comparative example and Example 1 is that it does not contain a swelling hydration accelerator. Specifically:
[0059] 1. Preparation of bearing grouting material:
[0060] 5 parts of PO52.5 ordinary Portland cement, 45 parts of R·FAC42.5 fast-hardening high-iron sulphoaluminate cement, 0 parts of expansive hydration accelerator, 2 parts of silica fume (0.3μm), 45 parts of quartz sand (10~20 mesh: 20~40 mesh: 50~100 mesh = 40%: 30%: 30%), 0.3 parts of polycarboxylic acid high-performance water reducer, 0.2 parts of sodium gluconate retarder, 0.02 parts of viscosity modifier (hydroxypropyl methylcellulose ether: L-galactose = 50:50), 0.1 parts of lithium carbonate early strength agent, and 0.2 parts of silicone defoaming agent.
[0061] Comparative Example 2
[0062] The difference between this comparative example and Example 1 is that the swelling hydration accelerator does not contain triisopropanolamine. Specifically:
[0063] 1. Preparation of swelling hydration accelerator:
[0064] Mix 60 parts of quicklime, 40 parts of overburned gypsum (calcined at 320°C), 0 parts of triisopropanolamine and 0.6 parts of sodium octadecanoate, and grind them in a mill for 30 minutes until the specific surface area is ≥350m 2 / kg, the obtained powder is the swelling hydration accelerator.
[0065] 2. Preparation of bearing grouting material:
[0066] 5 parts of PO52.5 ordinary Portland cement, 45 parts of R·FAC42.5 fast-hardening high-iron sulphoaluminate cement, 3 parts of expansive hydration accelerator, 2 parts of silica fume (0.3μm), 45 parts of quartz sand (10~20 mesh: 20~40 mesh: 50~100 mesh = 40%: 30%: 30%), 0.3 parts of polycarboxylic acid high-performance water reducer, 0.2 parts of sodium gluconate retarder, 0.02 parts of viscosity modifier (hydroxypropyl methylcellulose ether: L-galactose = 50:50), 0.1 parts of lithium carbonate early strength agent, and 0.2 parts of silicone defoaming agent.
[0067] Comparative Example 3
[0068] The difference between this comparative example and Example 1 is that the overburned gypsum in the expandable hydration accelerator is calcined at 500°C. Specifically:
[0069] 1. Preparation of swelling hydration accelerator:
[0070] Mix 60 parts of quicklime, 40 parts of overburned gypsum (calcined at 500°C), 1 part of triisopropanolamine and 0.6 parts of sodium octadecanoate, and grind them in a mill for 30 minutes until the specific surface area is ≥350m 2 / kg, the obtained powder is the swelling hydration accelerator.
[0071] 2. Preparation of bearing grouting material:
[0072] 5 parts of PO52.5 ordinary Portland cement, 45 parts of R·FAC42.5 fast-hardening high-iron sulphoaluminate cement, 3 parts of expansive hydration accelerator, 2 parts of silica fume (0.3μm), 45 parts of quartz sand (10~20 mesh: 20~40 mesh: 50~100 mesh = 40%: 30%: 30%), 0.3 parts of polycarboxylic acid high-performance water reducer, 0.2 parts of sodium gluconate retarder, 0.02 parts of viscosity modifier (hydroxypropyl methylcellulose ether: L-galactose = 50:50), 0.1 parts of lithium carbonate early strength agent, and 0.2 parts of silicone defoaming agent.
[0073] Comparative Example 4
[0074] The difference between this comparative example and Example 1 is that the fast-hardening high-iron sulphoaluminate cement is replaced with fast-setting and fast-hardening sulphoaluminate cement. Specifically:
[0075] 1. Preparation of swelling hydration accelerator:
[0076] Mix 60 parts of quicklime, 40 parts of overburned gypsum (calcined at 320°C), 1 part of triisopropanolamine and 0.6 parts of sodium octadecanoate, and grind them in a mill for 30 minutes until the specific surface area is ≥350m 2 / kg, the obtained powder is the swelling hydration accelerator.
[0077] 2. Preparation of bearing grouting material:
[0078] 5 parts of PO52.5 ordinary Portland cement, 45 parts of QR·SAC42.5 fast-setting and fast-hardening sulphoaluminate cement, 3 parts of expansive hydration accelerator, 2 parts of silica fume (0.3μm), 45 parts of quartz sand (10~20 mesh: 20~40 mesh: 50~100 mesh = 40%: 30%: 30%), 0.3 parts of polycarboxylic acid high-performance water reducer, 0.2 parts of sodium gluconate retarder, 0.02 parts of viscosity modifier (hydroxypropyl methylcellulose ether: L-galactose = 50:50), 0.1 parts of lithium carbonate early strength agent, and 0.2 parts of silicone defoaming agent.
[0079] Comparative Example 5
[0080] The difference between this comparative example and Example 1 is that it does not contain silica fume. Specifically:
[0081] 1. Preparation of swelling hydration accelerator:
[0082] Mix 60 parts of quicklime, 40 parts of overburned gypsum (calcined at 320°C), 1 part of triisopropanolamine and 0.6 parts of sodium octadecanoate, and grind them in a mill for 30 minutes until the specific surface area is ≥350m 2 / kg, the obtained powder is the swelling hydration accelerator.
[0083] 2. Preparation of bearing grouting material:
[0084] 5 parts of PO52.5 ordinary Portland cement, 45 parts of R·FAC42.5 fast-hardening high-iron sulphoaluminate cement, 3 parts of expansive hydration accelerator, 0 parts of silica fume (0.3μm), 45 parts of quartz sand (10~20 mesh: 20~40 mesh: 50~100 mesh = 40%: 30%: 30%), 0.3 parts of polycarboxylic acid high-performance water reducer, 0.2 parts of sodium gluconate retarder, 0.02 parts of viscosity modifier (hydroxypropyl methylcellulose ether: L-galactose = 50:50), 0.1 parts of lithium carbonate early strength agent, and 0.2 parts of silicone defoaming agent.
[0085] Comparative Example 6
[0086] The difference between this comparative example and Example 1 is that it does not contain a viscosity modifier. Specifically:
[0087] 1. Preparation of swelling hydration accelerator:
[0088] Mix 60 parts of quicklime, 40 parts of overburned gypsum (calcined at 320°C), 1 part of triisopropanolamine and 0.6 parts of sodium octadecanoate, and grind them in a mill for 30 minutes until the specific surface area is ≥350m 2 / kg, the obtained powder is the swelling hydration accelerator.
[0089] 2. Preparation of bearing grouting material:
[0090] 5 parts of PO52.5 ordinary Portland cement, 45 parts of R·FAC42.5 fast-hardening high-iron sulphoaluminate cement, 3 parts of expansive hydration accelerator, 2 parts of silica fume (0.3μm), 45 parts of quartz sand (10~20 mesh: 20~40 mesh: 50~100 mesh = 40%: 30%: 30%), 0.3 parts of polycarboxylic acid high-performance water reducer, 0.2 parts of sodium gluconate retarder, 0 parts of viscosity modifier, 0.1 parts of lithium carbonate early strength agent, and 0.2 parts of silicone defoaming agent.
[0091] Comparative Example 7
[0092] The difference between this comparative example and Example 1 is that the viscosity modifier is only hydroxypropyl methylcellulose ether. Specifically:
[0093] 1. Preparation of swelling hydration accelerator:
[0094] Mix 60 parts of quicklime, 40 parts of overburned gypsum (calcined at 320°C), 1 part of triisopropanolamine and 0.6 parts of sodium octadecanoate, and grind them in a mill for 30 minutes until the specific surface area is ≥350m 2 / kg, the obtained powder is the swelling hydration accelerator.
[0095] 2. Preparation of bearing grouting material:
[0096] 5 parts of PO52.5 ordinary Portland cement, 45 parts of R·FAC42.5 fast-hardening high-iron sulphoaluminate cement, 3 parts of expansive hydration accelerator, 2 parts of silica fume (0.3μm), 45 parts of quartz sand (10~20 mesh: 20~40 mesh: 50~100 mesh = 40%: 30%: 30%), 0.3 parts of polycarboxylic acid high-performance water reducer, 0.2 parts of sodium gluconate retarder, 0.02 parts of viscosity modifier (hydroxypropyl methylcellulose ether: L-galactose = 100:0), 0.1 parts of lithium carbonate early strength agent, and 0.2 parts of silicone defoaming agent.
[0097] Comparative Example 8
[0098] The difference between this comparative example and Example 1 is that the viscosity modifier is only L-galactose. Specifically:
[0099] 1. Preparation of swelling hydration accelerator:
[0100] Mix 60 parts of quicklime, 40 parts of overburned gypsum (calcined at 320°C), 1 part of triisopropanolamine and 0.6 parts of sodium octadecanoate, and grind them in a mill for 30 minutes until the specific surface area is ≥350m 2 / kg, the obtained powder is the swelling hydration accelerator.
[0101] 2. Preparation of bearing grouting material:
[0102] 5 parts of PO52.5 ordinary Portland cement, 45 parts of R·FAC42.5 fast-hardening high-iron sulphoaluminate cement, 3 parts of expansive hydration accelerator, 2 parts of silica fume (0.3μm), 45 parts of quartz sand (10~20 mesh: 20~40 mesh: 50~100 mesh = 40%: 30%: 30%), 0.3 parts of polycarboxylic acid high-performance water reducer, 0.2 parts of sodium gluconate retarder, 0.02 parts of viscosity modifier (hydroxypropyl methylcellulose ether: L-galactose = 0:100), 0.1 parts of lithium carbonate early strength agent, and 0.2 parts of silicone defoaming agent.
[0103] During construction, the above-mentioned embodiments and comparative examples are respectively added with water and stirred into slurry for use (the weight ratio of water to the dry powder mortar of this product is 0.13). The test results of various properties are shown in Table 1. The technical requirements are based on Appendix H of TB / T 3320-2013 "Spherical bearings for railway bridges", the water seepage rate is tested according to GB / T 50080-2016 "Standard test method for performance of ordinary concrete mixtures", the fluidity is tested according to Appendix A of GB / T50448-2015 "Technical specification for application of cement-based grouting materials", the flexural strength and compressive strength are tested according to GB / T 17671-2021 "Test method for strength of cement mortar (ISO method)", the elastic modulus is tested according to JGJ / T 70-2009 "Standard test method for basic properties of building mortar", and the free expansion rate is tested according to JC / T313-2009 "Test method for expansion rate of expansive cement".
[0104] Table 1 Performance test results of the embodiments and comparative examples
[0105]
[0106] The results show that the high flexural and high early strength bearing grouting materials of Example 1, Example 2, Example 3 and Example 4 have ultra-high 24h early flexural strength, high compressive strength, high fluidity, self-flowing and compacting, good resistance to water seepage and segregation, micro-expansion, and good long-term durability.
[0107] The flexural and compressive strengths of Comparative Example 1 were significantly reduced, indicating that the swelling hydration accelerator had a great influence on the flexural and compressive strengths.
[0108] The flexural and compressive strengths of Comparative Example 2 also decreased to a certain extent, indicating that the triisopropanolamine in the expandable hydration accelerator also has a great influence on the flexural strength performance.
[0109] The flexural and compressive strengths of Comparative Example 3 decreased significantly, indicating that the calcination temperature environment of the overburned gypsum also has a great influence on the flexural strength performance.
[0110] The flexural strength of comparative example 4 also decreased to a certain extent, indicating that different sulphoaluminate cements also have a great influence on the flexural strength performance.
[0111] The flexural strength of Example 5 also decreased to a certain extent, and there was also a slight water seepage, indicating that silica fume has a certain influence on the flexural strength and working performance.
[0112] Comparative Examples 6, 7 and 8 have water seepage, resulting in poor workability of the bearing grouting material. It will also affect the flexural and compressive strengths, causing the flexural and compressive strength performances to decline. This shows that the proportion and type of viscosity modifier have a great influence on the workability of the bearing grouting material, and will also affect other properties.
[0113] To sum up, scientific and reasonable compounding is a necessary condition for preparing bearing grouting materials with excellent performance. When the components of the high flexural and high early strength bearing grouting materials of the present invention reach a scientific balance condition, they can exert the best synergistic effect, so that it has the characteristics of ultra-high early flexural strength, high compressive strength, high fluidity, self-flowing and compacting, good resistance to water seepage and segregation, micro-expansion, and good long-term durability. It has excellent working performance and mechanical properties and is suitable for gravity grouting of spherical bearings of railway bridges and highway bearings.
Claims
1. A bearing grouting material, characterized in that: It includes the following components by weight: 5~20 parts of ordinary Portland cement; 30-50 parts of rapid hardening high iron sulphoaluminate cement; 3-5 parts of swelling hydration accelerator; Silica fume 2~6 parts; 30~50 parts of quartz sand; Superplasticizer 0.2~0.6 parts; Retarder 0.2~0.5 parts; Viscosity modifier 0.01~0.03 parts; Early strength agent 0.04~0.2 parts; Defoaming agent 0.1~0.3 parts; The swelling hydration accelerator is prepared by mixing quicklime, over-burned gypsum, triisopropanolamine and sodium octadecanoate, and grinding the mixture in a mill until the specific surface area is ≥350m 2 / kg; the overburned gypsum is made by roasting at 300-350°C; The viscosity modifier is a complex of hydroxypropyl methylcellulose ether and L-galactose; The mass ratio of quicklime, overburned gypsum, triisopropanolamine and sodium octadecanoate is 60-80:20-40:1-3:0.6-1.0; The mass percentage of the hydroxypropyl methylcellulose ether and L-galactose is 40-60%:40-60%.
2. The bearing grouting material according to claim 1, characterized in that: The CaO content in the quicklime is ≥60%.
3. The bearing grouting material according to claim 1, characterized in that: The particle size of the silica fume is 0.2-0.4 μm.
4. The bearing grouting material according to claim 1, characterized in that: The quartz sand is compounded by quartz sand of 10-20 mesh, 20-40 mesh and 50-100 mesh, and the mass percentages thereof are 30-55%: 20-40%: 15-35% respectively.
5. The bearing grouting material according to claim 1, characterized in that: The superplasticizer is a polycarboxylic acid high performance water reducing agent.
6. The bearing grouting material according to claim 1, characterized in that: The retarder is at least one of tartaric acid, boric acid and sodium gluconate.
7. The bearing grouting material according to claim 1, characterized in that: The early strength agent is at least one of lithium carbonate, lithium sulfate and calcium formate.
8. The bearing grouting material according to claim 1, characterized in that: The defoamer is an organosilicon defoamer.
Citation Information
Patent Citations
Early strength grouting material
CN101786838A
Grouting material for reinforcing rubble masonry
CN117756472A